บทบาทของซิลิเอตกลุ่มทินทินนิดต่อสายใยอาหารบริเวณชายฝั่งจังหวัดสมุทรสาคร - ทัศนธร ภูมิยุทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Tintinnids are protozoa that belong to Phylum Ciliophora and Suborder Tintinnida. Key feature of this protozoan is outer shell called "lorica". Tintinnids prey on pico and nanophytoplankton. Moreover, tintinnids are also the prey of other zooplankton. Thus tintinnids are important links between microbial loop and pelagic food web. However, there is limited number of tintinnid study. Nine sampling stations were set up for the measurements of physico-chemical parameters as well as plankton sampling during four different periods between 2012 and 2013 to cover seasonal variation of the monsoons and inter-monsoon periods. Tintinnid samples, water sampler for size fractionation chlorophyll_a and zooplankton samples were collected. Thirty one species from 11 genera of tintinnids were recorded with the diversity index in the range of 0.53 – 1.03. Tintinnopsis is the genus that has highest species numbers. Tintinnids abundance ranges from 3.50 x 101 -1.63 x 103 cells/l. Phytoplankton biomass in the form of chlorophyll_a is in the range of 1.500 – 509.4 µg/l with 78% belong to nanophytoplankton. Overall zooplankton density are up to 3.8 x 106 individuals/100 m3 in early north-east monsoon season. Species component analysis using Multidimensional scaling (MDS) indicates that tintinnid in this study can be divided into 4 groups. Population of tintinnid in late north-east monsoon season significantly correlates with nanophytoplankton chlorophyll_a and population in summer or inter-monsoon season has lowest density in contrast to high density of calanoid copepods Acartia spp. The result show ecological role of tintinnids as primary consumer of small phytoplankton and being food for microzooplankton and certian mesozooplankton in this area.